Synthesis, Molecular Docking and Biological Evaluation of New Quinoline Analogues as Potent Anti-breast Cancer and Antibacterial Agents: Synthesis and Biological Evaluation of New Quinoline Analogues - V. Rathod, Shrimant; W. Shinde, Kailas; S. Kharkar, Prashant; P. Shah, Chetan (Iranian Journal of Pharmaceutical Sciences, 2020)
A series of new class of quinoline analogues were synthesized from isatin through two steps in good yields. All compounds were further evaluated for their anticancer activity against triple-negative breast cancer cell line (MDA-MB-231) using MTT assay and antibacterial activity against Gram-positive bacteria (Staphylococcus aureus 6538p and Bacillus subtilis) and Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa) using agar well diffusion method. All synthesized compounds were confirmed by spectral characterization viz FT-IR, MS, 1H-NMR, and 13C-NMR. Results indicated that in vitro anticancer evaluation, IC50 values of all target compounds were in the range of 11.50-37.99 μM and compound 4h showed better promising anti-breast cancer activity among all synthesized derivatives. In vitro antibacterial evaluation, compounds 4d, 4f, 4h, and 4j showed moderate antibacterial activity among all derivatives. Molecular docking analysis demonstrated good interaction of compound 4h with the active site residue of Human Carbonic Anhydrase I, Protein Kinase A, and Kinesin Spindle Protein (KSP).